2009
DOI: 10.1007/s11771-009-0125-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic depressant lignosulfonate calcium on separation of chalcopyrite from pyrite

Abstract: In order to selectively separate chalcopyrite from pyrite,the effect of organic depressant lignosulfonate calcium (LSC) on the flotation separation of chalcopyrite from pyrite was investigated by flotation tests. The depression mechanism was studied by Fourier-transform-infrared (FTIR) analysis. The flotation tests of single mineral show that LSC can depress the flotation of pyrite in a certain pH range, but it has little effect on chalcopyrite flotation. Flotation separation of a mixture of chalcopyrite and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…However, large dosages were required to achieve effective depression of pyrite flotation. Another study conducted by Liu et al (2009) showed that lignosulfonate calcium (LSC) depressed pyrite flotation in a wide pH range.…”
Section: Lignosulfonate-based Biopolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, large dosages were required to achieve effective depression of pyrite flotation. Another study conducted by Liu et al (2009) showed that lignosulfonate calcium (LSC) depressed pyrite flotation in a wide pH range.…”
Section: Lignosulfonate-based Biopolymersmentioning
confidence: 99%
“…In contrast, the presence of Ca 2+ in large quantities may weaken the biopolymers' ability to inhibit xanthate adsorption due to the stronger complexing affinity of biopolymers towards Ca 2+ in solution. Liu et al (2009) found that the selective depression of pyrite in the flotation of chalcopyrite-pyrite mixtures was due to the preferential adsorption of lignosulfonate calcium (LSC) on pyrite surface and little adsorption on chalcopyrite based on the FTIR analysis. The selective adsorption of LSC on pyrite occurred due to interactions between the oxidized species Fe(OH) 3 on pyrite surface and the ASO À 3 in LSC.…”
Section: Lignosulfonate-based Biopolymersmentioning
confidence: 99%
“…The depression of pyrite flotation by the biopolymers indicates that the biopolymers make the pyrite surface more hydrophilic with a smaller contact angle. In another study, it was found that lignosulfonate calcium (LSC) depressed pyrite flotation in a certain pH range and had little effect on chalcopyrite flotation [16]. The depression mechanism was attributed to the competitive adsorption of LSC and xanthate on pyrite surface.…”
Section: Introductionmentioning
confidence: 99%
“…It was assumed that LSC was adsorbed on pyrite surface through the interaction between hydroxylated metallic sites of pyrite and functional groups of the lignosulfonate calcium. This adsorption may inhibit the adsorption of collector, turn the pyrite surface hydrophilic and then depress pyrite in a flotation process [14,16]. However, this assumption has not been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the use of inorganic depressants such as cyanides, sulphites, or ferrocyanides has raised concerns on environmental grounds. Therefore, organic polymers have been studied, in view of their natural, biodegradability and non-toxicicity (Lopez-Valdivieso et al, 2004;Bicak et al, 2007;Liu et al, 2009;Bulut et al, 2011;Koleini, Abdollahy, and Soltani, 2012;Sarquís et al, 2014;Mu, Peng, and Lauten, 2015). However, there is currently a lack of knowledge about the interaction between these additives and solid surfaces in highly saline environments.…”
mentioning
confidence: 99%